A influência da atividade física nos parâmetros da marcha durante atividades de dupla tarefa em idosos - Andrade, Verônica Filter DE (My University, 2023)
Objective: To analyze the possible differences in the kinematic variables of gait between physically active and physically inactive elderly people while performing dual-task activities. Methodology: Observational, analytical, and cross-sectional study, in which elderly individuals, aged between 60 and 75 years, participated, divided into two groups: physically inactive group (IG) and physically active group (AG). Participants were equally grouped into ten female and male individuals, classified using the IPAQ (International Physical Activity Questionnaire). Participants initially performed simple tasks (arithmetic, verbal fluency, and gait) and then performed dual task activities, associating gait with the two cognitive activities (arithmetic and verbal fluency). From this, the variables velocity, cadence, stride length, stride width, stride time and double support were collected. To compare variables according to task and group, the Generalized Estimating Equations (GEE) model complemented by the Bonferroni test was used. As a decision criterion, the significance level adopted was p<0.05. Results: In the intragroup analysis, where the effect of dual tasks on gait was verified, both groups showed significant decreases in velocity, cadence, stride width, stride time and double support, both in the arithmetic dual task and in the verbal fluency dual task. However, in the comparisons between the groups, there were no statistically significant differences in any kinematic parameter analyzed, both in the single gait analysis and in the dual tasks. Conclusion: The dual tasks had a negative influence on the kinematic gait parameters in both groups. However, the level of physical activity could be considered a factor that minimizes the effects of the dual task on gait in the elderly. [resumo fornecido pelo autor]
Keywords: Aptidão física em idosos; Qualidade de vida; Capacidade motora; Envelhecimento; Physical fitness for older people; Quality of life; Motor ability; Aging